2007
DOI: 10.1093/ageing/afm032
|View full text |Cite
|
Sign up to set email alerts
|

Health conditions, health symptoms and driving difficulties in older adults

Abstract: Objectives: previous research has indicated that age-related medical or health conditions can affect driving performance in older adults but little, if any, research has examined the mechanisms through which health conditions affect driving difficulties in older adults. Design: cross-sectional, correlational study. Setting: random sample from the community. We examined the nature of the relations among health conditions, healthrelated symptoms, physical fitness levels and specific types of self-reported drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…The maintenance of mobility among older adults is a growing area of concern, and transportation mobility is an important source of independence for older adults (Dickerson et al, 2007;Tuokko et al, 2007). In the present study, a specific exercise program that incorporated open skills and more demanding perceptive and cognitive activities than many of the traditional closed and cyclic physical activities was successful in improving several abilities considered critical for driving performance and safety among older adults.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The maintenance of mobility among older adults is a growing area of concern, and transportation mobility is an important source of independence for older adults (Dickerson et al, 2007;Tuokko et al, 2007). In the present study, a specific exercise program that incorporated open skills and more demanding perceptive and cognitive activities than many of the traditional closed and cyclic physical activities was successful in improving several abilities considered critical for driving performance and safety among older adults.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have found associations between physical activity or mobility with driving (Marottoli et al, 2007; and have also reported that physical activity (or the lack of) is a modifiable factor that is driving-related through its relevance on several health conditions or symptoms (Taylor and Dorn, 2006;Tuokko et al, 2007). Nevertheless, the research approach that emphasises the influence of physical activity on driving capability has been specific, studying associations between the driving task and motor functions (often in populations with some type of impairments) and has not assumed a broader perspective that intends to achieve beneficial exercise effects on several abilities relevant for driving performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuokko et al [115] found that older adults with lower physical activity levels had evident driving difficulties involving the spine and lower body. They suggested that physical activity focused on the improvement of spinal flexibility could enhance specific aspects of driving performance, such as turning to check for traffic or operating a seat belt.…”
Section: Physical Functioningmentioning
confidence: 99%
“…Sims, McGwin, Allman, Ball, and Owsley (2000) found that self-reported difficulty with yard work, light housework, and opening a jar was correlated with a higher relative risk of crash. Tuokko, Rhodes, and Dean (2007) found that symptoms of health problems experienced in specific body regions were more clearly related to difficulties in driving that were associated with those areas of the body. For example, health symptoms involving the lower body were associated with self-reported difficulties applying the brake or stepping into a vehicle.…”
mentioning
confidence: 99%